If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 6 + 3r = 8r + -14 Reorder the terms: 6 + 3r = -14 + 8r Solving 6 + 3r = -14 + 8r Solving for variable 'r'. Move all terms containing r to the left, all other terms to the right. Add '-8r' to each side of the equation. 6 + 3r + -8r = -14 + 8r + -8r Combine like terms: 3r + -8r = -5r 6 + -5r = -14 + 8r + -8r Combine like terms: 8r + -8r = 0 6 + -5r = -14 + 0 6 + -5r = -14 Add '-6' to each side of the equation. 6 + -6 + -5r = -14 + -6 Combine like terms: 6 + -6 = 0 0 + -5r = -14 + -6 -5r = -14 + -6 Combine like terms: -14 + -6 = -20 -5r = -20 Divide each side by '-5'. r = 4 Simplifying r = 4
| -5n+7n=8 | | 12.50x=75 | | -3(6.2-x)=-11.1 | | 4x^2+64y^2=0 | | 10x=10x-2+2 | | 2(5)(6.5)/2 | | -x=x+2 | | 16x-3.8=0.2 | | 10+x=4-(x+2) | | 5n-2=15 | | -118=-7(2-3r)+5r | | -3/4(4-x)=-24 | | 3(7x-3)=-26+4x | | 4k-4(1-5k)=-148 | | 0.12(x-4200)=3000 | | 15+7.50x=75 | | 4x-2(3x+9)-8-4x+2= | | -10x+3=-x+12 | | 3/8g-1/3=-10/3 | | 8g-7=1 | | 11w=9w+12 | | 1/2(x+10)=25 | | -20=-3x-5 | | -2y+10=5x | | (-2x)+16=4x-8 | | x^2/3-2x^1/2-3=0 | | 3u=45-2u | | -1/3=r-34 | | 5(a-4)=2a+2a+3a+20 | | 0.4h+1=16-1.14 | | f(1)=9 | | h*h+2.5*2.5=7*7 |